Adoption Of The Use Of Refugia Plants As Integrated Pest Control For Chili Farmers In Cilawu District, Garut Regency - Windy Tamara Ayu; Dedy Kusnadi; Wahyu Trisnasari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
Pests attack at Cilawu Subdistrict had increases cases, pests attack because of climate change. The adoption of integrated pest control technology in Cilawu District is relatively low, so a strategy is needed to increase the level of application of horticultural commodity technology. This study analyze the level of farmer adoption of refugia plant as Integrated Pest Controls (IPM), identified factors caused an strategies adoption of refugia plant use at chili farmer. This study held on April till June 2021 used intstrument questionnaire to collect all data and analize used descriptive an reggresion. The research data consisted of primary data with data collection plus interviews with chili farmers, and secondary data from local institutions. The primary data analysis method used descriptive and regression analysis. The study involved 61 people as research respondents who were members of farmer groups. The adoption of integrated pest control technology in Cilawu District is low so there is a need for a strategy to increase the level of application of horticultural crop commodity technology. The adoption level of technology at Cilawu Subdistrict are low level and need improvement to raise the tecnology horticultural cultivation. Pests controls use the refugia plant push the balances of ecosystem an decrease the pests attact. The result of the analysis showed adoption of technology are high. Factors affect the adoption are number of family and the information services. Strategies to improve level of adoption based on analaysis to increase the adoption are information strenghtening by exstension, discussion an by model demo plot.